2021
DOI: 10.1080/15412555.2021.1975670
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Assessment in a Stable COPD Cohort: Is There a COPD-Frail Phenotype?

Abstract: The frailty syndrome increases the morbidity/mortality in older adults, and several studies have shown a higher prevalence of this syndrome in patients with Chronic Obstructive Pulmonary Disease (COPD). The aim of this study was to identify the characteristics of frail patients with COPD to define a new phenotype called "COPD-frail." We conducted a cross-sectional study in a cohort of patients with stable COPD, classified as either frail, pre-frail, or non-frail. Sociodemographic, clinical, and biochemical var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 28 publications
(42 reference statements)
2
42
0
Order By: Relevance
“…Data from 10 studies [ 11 , 22 24 , 26 , 27 , 29 , 32 , 33 , 35 ] involving 2,392 participants were available for meta-analysis of CAT score, showing that those with frailty presented higher CAT score than those without frailty [mean difference 6.20(95%CI 4.43 to 7.96); I 2 = 84.95%, Fig. 3 B].…”
Section: Resultsmentioning
confidence: 99%
“…Data from 10 studies [ 11 , 22 24 , 26 , 27 , 29 , 32 , 33 , 35 ] involving 2,392 participants were available for meta-analysis of CAT score, showing that those with frailty presented higher CAT score than those without frailty [mean difference 6.20(95%CI 4.43 to 7.96); I 2 = 84.95%, Fig. 3 B].…”
Section: Resultsmentioning
confidence: 99%
“…In a cohort of individuals (age ≥40) with stable COPD, Naval et al found approximately 40% of individuals identified as frail using the Fried phenotype also had more severe BODE scores. 61 Using a deficit accumulation definition of frailty, Scarlata et al showed a strong correlation ( r =0.53) between frailty and BODE scores among stable COPD patients age 60 or older. 62 …”
Section: Discussionmentioning
confidence: 99%
“…34 In addition, previous studies have shown that pre-frail and non-frail patients have different physical activity, and may play a significant role in morbidity and mortality. 12,13,[35][36][37] In particular, a poor performance in the 5-STS has been shown to be a predictor of re-hospitalization 31 and survival in COPD patients. 35 However, hypotheses about timing and length of stay remained to be confirmed.…”
Section: Discussionmentioning
confidence: 99%